OsHOX1 and OsHOX28 Redundantly Shape Rice Tiller Angle by Reducing HSFA2D Expression and Auxin Content. Issue 3 (10th September 2020) - Hu, Yong; Li, Shuangle; Fan, Xiaowei; Song, Song; Zhou, Xin; Weng, Xiaoyu; Xiao, Jinghua; Li, Xianghua; Xiong, Lizhong; You, Aiqing; Xing, Yongzhong
Abstract : Two homeodomain-leucine zipper genes shape tiller angle of rice by influencing lateral asymmetric distribution of the plant hormone auxin. Abstract: Tiller angle largely determines plant architecture, which in turn substantially influences crop production by affecting planting density. A recent study revealed that HEAT STRESS TRANSCRIPTION FACTOR2D ( HSFA2D ) acts upstream of LAZY1 ( LA1 ) to regulate tiller angle establishment in rice ( Oryza sativa ). However, the mechanisms underlying transcriptional regulation of HSFA2D remain unknown. In this study, two class II homeodomain-Leu zipper genes, OsHOX1 and OsHOX28, were identified as positive regulators of tiller angle by affecting shoot gravitropism. OsHOX1 and OsHOX28 showed strong transcriptional suppressive activity in rice protoplasts and formed intricate self- and mutual-transcriptional negative feedback loops. Moreover, OsHOX1 and OsHOX28 bound to the pseudopalindromic sequence CAAT(C/G)ATTG within the promoter of HSFA2D, thus suppressing its expression. In contrast to HSFA2D and LA1, OsHOX1 and OsHOX28 attenuated lateral auxin transport, thus repressing the expression of WUSCHEL-RELATED HOMEOBOX 6 ( WOX6 ) and WOX11 in the lower side of the shoot base of plants subjected to gravistimulation. Genetic analysis further confirmed that OsHOX1 and OsHOX28 act upstream of HSFA2D . Additionally, both OsHOX1 and OsHOX28 inhibit the expression of multiple OsYUCCA genes and decrease auxin biosynthesis. Taken together, these results demonstrated that OsHOX1 and OsHOX28 regulate the local distribution of auxin, and thus tiller angle establishment, through suppression of the HSFA2D - LA1 pathway and reduction of endogenous auxin content. Our finding increases the knowledge concerning fine tuning of tiller angles to optimize plant architecture in rice.